Moonstruck: Viewing the Moon in the Ottoman World of the Seventeenth Century. (November 2019) - Yaşa, Fırat
Time is the only phenomenon that encompasses the past, present, and future, giving vitality to all living beings. Throughout history, people have tried to understand this phenomenon by determining its cycles and dividing them into segments. In pre-modern societies, the powerlessness of people against nature made them view time and space as closely connected (time-space continuum). In traditional Ottoman society, it was thus difficult to measure time. People made calculations using lunar movements. Court astrologers observed the moon and stars, advising sultans when to hold imperial accession ceremonies, celebrate princely births and weddings, or launch ships. In larger towns, at least the prayer times could be determined with assurance: However, villagers were mostly aware only of the day, month, season, and year. Hence, the understanding of time was quite different on the higher and lower rungs of the social ladder. In this paper, I attempt to answer the following questions: To what extent is it possible to measure time by studying the phases of the moon? What were the meanings that the Ottoman ruling class attached to the moon? For what reasons did ordinary people try to document in the qadi court at what time they saw the new moon, finding witnesses and having the court scribes record their testimonies? My sources are the qadi court records of Anatolian and Crimean cities, with additional information from travelogues and chronicles.